Adesão à antibioticoprofilaxia cirúrgica para pacientes pediátricos em hospital universitário - Jose Carlos Matos (2011)
Introduction: It is estimated that more than half of surgical site infections can be prevented through the proper implementation of recommendations based on scientific evidence, especially for surgical antibiotic prophylaxis. Adherence to recommendations for appropriateuse of surgical antibiotic has been extensively studied in adults, but studies involving only pediatric patients are rare in the literature. Objectives= To assess adherence to the "Guidelines for Surgical Antibiotic Prophylaxis" of Hospital das Clinicas, Universidade Federal de Minas Gerais, with recommendations for pediatric patients undergoing surgical procedures NISS (National Infection Surveillance System), to identify factors associated with inappropriate use of antibiotics prophylactic and determine whether it was a factor associated with surgical site infection (SSI). Method: A cross sectional study from a cohort of 730 pediatric patients, drawn to a previous study of risk factors for surgical site infections. The data were supplemented by reviewing patients' records. Following or not following the local Surgical Antibiotic Prophylaxis Guidelines" were evaluated according to= indication, choice of antibiotic, dose, interval, intraoperative dose, timing of first dose and duration of antibiotic prophylaxis. It was considered inappropriate use (non-compliance) when the recommendation for any of these parameters was not followed. Univariate and multivariate analysis were performed to identify variables that predicted adherence and predictors of surgical siteinfection between patient-specific factors, the surgical procedure and the surgical team. For univariate analysis it was used the chi-square test to assess the association of predictor variables with compliance to the guide and with the same variables with surgical site infection, and variables were considered significant with p <0.05. For logistic regression we selected the variables with p <0.20 in univariate analysis. In the final model statistical significance were considered with p <0.05. Results: Of 720 pacients most were male (68.5%, n = 493), mostly between ages 1 and 5 years (36%) and over 5 years (38%). Emergencyprocedures occurred in 18% (n = 132) of patients, community infection in 6.9% (n = 50) and 6.8% (n = 49) were immunocompromised. The preoperative time was less than or equal to 24 hours in 73.9%. According to the Index of Risk of Surgical Infection (IRIC) 67.9% of patients were classified as zero IRIC. The team of surgeons were responsible for 82.5% (n = 594) of the surgical procedures. Most common surgeries were inguinal (30.1%) and genitourinary surgery (24%). Cephalothin was the most prescribed antibiotic (81.9%). Compli to the indication of prophylactic antibiotics in 86.7% (n = 624), the choice of drug in 93% (n = 294), the dose in 68% (n = 215) and the dose interval in 98.5 % of prescriptions. The lowest rates of compliance were to intraoperative dose (36%), timing (34.2%) and duration of prophylactic antibiotics (45.7%). Adherence to all the recommendations for surgical antibiotic prophylaxiswas 45.7%. There was inappropriate use of the Guide in 54.3% of prescriptions. The median length of stay and time after surgery was higher among the cases of non-adherence (p <0.001). In multivariate logistic regression analysis were significant (p <0.05) proceduresperformed in emergency (OR= 5.6), IRIC = 1 (OR= 6.84) and IRIC = 2 (OR= 3.04), presence of community infection (OR= 2.77) and pre-operative time> 24 hours (OR= 3.79). In multivariate analysis with ISC as the dependent variable were significant age (<28days of life= OR= 4.24), the IRIC = 1 (OR= 1.89) and IRIC = 2 (OR= 2.24) and non-adherence to Surgical Antibiotic prophylaxis Guide (OR= 2.79). Conclusion: emergency procedures, preoperative time greater than 24 hours, classification 1 or 2 of IRIC and presence of previous infection were factors significantly associated with inappropriate use of Surgical Antibiotic Prophylaxis Guide. We identified increased chance of developing SSI for patients aged less than or equal to 28 days, for risk index (IRIC) 1 or 2 and for inappropriate surgical antibiotic prophylaxis. Surgical Antibiotic Prophylaxis Guides misuse has determined a risk ofdeveloping surgical site infection was 2.79 times higher than for patients for whom the guide was used properl